Generation Gap; Analisa Pengaruh Perbedaan Generasi Terhadap Pola Komunikasi Organisasi di Perusahaan Consumer Goods Di Kota Surabaya - Gabriella Sagita Putri; Bobie Hartanto; Nisrin Husna (Universitas Merdeka Madiun, 2019)
In a professional world, organizational communication is one element to support their business activity, the relationship between employees and managers of various line interconnected through communication. One of the problems relating to communication in the organization is generation gap that are confronted by having different perceptions, behavior and character involving employees across the generations in one company. This research going to see the influence of the generational differences between employees was born from generation x and generation y or milenials of different positions positions in companies engaged at consumer goods industry in Surabaya. The research objective is to explain Impact of the existence of the generational difference against the pattern of organizational communication among employees in companies. This research with eksplanative be held with quantitative approach, data collection is gathered through interview with quitionnaire. The result explained that correlation analysis of 17,64% from pearson product moment, it means there is low influence but significant between generational differences and pattern of communication organization. Significance tested of thitung (2,37) > ttabel (1,42), then Hi accepted.